Additional problems - Schwartz, Howard F. (International Center for Tropical Agriculture, 1989)
Many factors can severely affect beans during their growth cycle. Parasitic plants, such as Cuscuta epithymum and Cassytha filiformis, can reduce yields. Various environmental conditions including frost, extreme conditions of high or low MC, sudden changes in soil and air temp., and periods of intense sunlight and wind can damage bean seedlings or mature plants. Variations in soil properties and drainage may produce marked differences in plant appearance and vigor. Genetic and physiological abnormalities may cause obvious or subtle change in plant development. Improper pesticide and fertilizer applications and toxic air pollutants may cause chemical damage. Sometimes the symptoms produced by these factors are confused with those produced by insects, diseases, nematodes, and nutritional disorders. A complete history of all factors relevant to bean production in a specific region is required to identify the causal agent correctly. (CIAT)